Determinan Insiden Preeklamsia pada Ibu Primigravida - Sofia Rhosma Dewi; Rosidawati Ningsih; Muttimatur Rifah; Dwi Resti Alfioni; Rumaisya Milhan Al Hajj; Fitria Arisma Dahlia (Poltekkes Kemenkes Kupang, 2022)
Background: Preeclampsia is a complication in pregnancy that has three main symptoms, namely gestational hypertension > 140/90 mmHg, edema, and protein in the urine > 3 grams and often occurs during pregnancy, childbirth and even in postpartum women. In the Sustainable Development Goals (SDGs), the MMR target is 70 per 100,000 live births in 2030. The problem of this research is the factors associated with the incidence of preeclampsia in pregnant women. This study aims to determine the factors that cause the incidence of preeclampsia in pregnant women. Method : used in this study is a literature review by analyzing a number of specified articles. In this study, 10 articles were used on preeclampsia and pregnancy. Results : from of the literature review analysis, it was concluded that there are many factors that cause preeclampsia in pregnant women, namely age, parity, primigravida and multiparous pregnancies, obesity, BMI, history of PEB and hypertension, and irregular ANC visits. influence the occurrence of preeclampsia in pregnant women. Conclusion: With this factor, it is expected to be a screening in handling cases of preeclampsia in the field and improving maternal health in reducing MMR in Indonesian.